KEANEKARAGAMAN JENIS SATWALIAR DI KAWASAN PERKEBUNAN KELAPA SAWIT DAN STATUS PERLINDUNGANNYA: STUDI KASUS DI KAWASAN UNIT PENGELOLAAN PT. AGRO KARYA PRIMA LESTARI - Harnios Arief; Yanuar Wicaksono; Domi Suryadi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
Degradation of ecosystems in the region of Agro Karya Prima Lestari Ltd causing this region un function well as wildlife habitat. This is indicated by the low level of wildlife encounters, both on observations during this study took place as well as from interviews with some of the people who live in the area. Based on the results of field observations during the course of the study, it is known there are 19 species of mammals, 47 species of birds and 5 species of reptiles. Based on the results of the analysis, it is known that this area contains 10 species of mammals, 16 species of birds and four species of reptiles that includes the category of rare / protected. Keywords: ecosystem, habitat, wildlife, and wildlife species diversity.